AN ADAPTED INTERVENTION RESEARCH MODEL: SUGGESTIONS FOR RESEARCH AND PRACTICE - Strydom, H; Steyn, M M; Strydom, C (Social Work/Maatskaplike Werk, 2007)
The various existing models of intervention research all have advantages and disadvantages. Postgraduate students, and especially doctoral students in Social Work, have on many occasions expressed their dilemma in choosing a specific model of research for intervention procedures. Therefore, many have used the intervention research model or the developmental research and utilisation model, while others have adapted these models to suit their specific research endeavours. After making a careful study of these two models, an adapted intervention research model will be suggested for use in studies of a combined research and practice nature.